MODAL SOSIAL KELOMPOK USAHA BERSAMA (KUBE) PADA PROGRAM KELUARGA HARAPAN (PKH) DI NAGARI SUNGAYANG KECAMATAN SUNGAYANG KABUPATEN TANAH DATAR - Novlin Moninda; Hesti Asriwandari (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
This study entitled "Social Capital of the Joint Business Group in the Family Hope Program at Nagari Sungayang, Sungayang District, Tanah Datar Regency." Researchers are very interested in determining this theme because of the importance of the role of social capital in a group. Data analysis in this study is by using descriptive quantitative methods, which concerns the role of social capital in joint venture groups (KUBE) which will then be analyzed using social capital theory. As for the formulation of the problem in this study, namely (1) What is the role of the elements of social capital in the activities of the collective business group (KUBE) in PKH? (2) What are the barriers to each of the elements of social capital in the joint venture group (KUBE) in PKH? Data collection techniques in this study were questionnaires and documentation. As for the population and samples using the Slovin technique from 165 populations, 62 samples were obtained and the findings in the field can be seen that the role of social capital in the KUBE group, namely the elements of social capital norms and networks, is in the medium category and trust is in the low category. Meanwhile, the obstacle to the elements of social capital in the joint business group (KUBE) is trust. Keywords: Social Capital, KUBE, Hope Family Program